Human Leptospirosis Outbreak: A Year After the ‘Cempaka' Tropical Cyclone - Nur Lathifah Syakbanah; Anis Fuad (Universitas Airlangga, 2021)
Introduction: The ‘Cempaka' Tropical Cyclone hit south Java in November 2017, causing heavy rainfall and severe flooding. Changes in climate variability and extreme weather events may shift the geographic and seasonal patterns of neglected tropical diseases such as leptospirosis. This study analyses the Spatiotemporal pattern between flooding, weather, and human leptospirosis cases after a tropical cyclone. Methods: This was an ecological study that collected monthly flooding data, weather data, and human leptospirosis data cases per village from November 2017 to October 2018, a year after the ‘Cempaka' Tropical Cyclone in Bantul. Spatio-temporal analyses were calculated to 0-3 months lag by Pearson's correlation, spatial mapping, and time-series graphs. Results and Discussion: As many as 99 people infected with leptospirosis were found in all 75 villages in Bantul. The villages affected by flooding were 44% and leptospirosis cases spread in 68% of villages. A 1-month lag (r = 0.6849; p < 0.05) and 3-months lag (r = 0.6666; p < 0.05) of relative humidity along with a 1-month lag (r = 0.7451; p < 0.05) and 3-months lag (r = 0.8561; p < 0.05) of rainfall were found to be correlated to human leptospirosis cases. Heavy rain due to the Cempaka Tropical Cyclone caused flooding and transmission of Leptospira bacteria into the water and heightened contact between humans, animals, and the environment. Conclusion: It is found that flooding, relative humidity, and rainfall after the Cempaka Tropical Cyclone would be followed by human leptospirosis outbreaks 1 and 3 months later. Cross-sectoral cooperation of public health authorities should integrate climatic information as an early warning for disaster-prone areas and community groups at risk.